Impact of sequential administration of detomidine, butorphanol, and midazolam on sedation, ataxia, stimulus response, and bispectral index in horses - Thorn, Caitlin A.; Wilson, Deborah V.; Wang, Sichao; Horne, William A. (Frontiers in Veterinary Science, 2025)
BackgroundStanding sedation is a safe and cost-effective alternative to general anesthesia in horses, but challenges include achieving adequate drug effect to block the stimulus response without inducing ataxia or recumbency. A benefit of midazolam has been reported in equine dental procedures. Seeking synergy, a combination of lower doses of several pharmacologic agents, including midazolam, may improve the quality of sedation while minimizing adverse effects. Bispectral index (BIS) correlates with sedation scores in human ICU patients, but the correlation between sedation scores and BIS has not been evaluated in horses.ObjectiveThis study aimed to evaluate observational sedation scores and BIS in horses sequentially administered low-dose detomidine, butorphanol, and midazolam bolus and constant rate infusions (CRIs).MethodsFifteen healthy horses received a standardized sedation protocol with sequential bolus doses and CRIs of detomidine, butorphanol, and midazolam. Sedation was assessed using a numerical rating scale that evaluated depth/stimulus response and postural instability/ataxia, and BIS was recorded at the same time points. Linear mixed-effect models assessed treatment effects; correlations between BIS and sedation scores were calculated within and between horses.ResultsSedation scores increased significantly with each drug added. The addition of midazolam increased sedation depth/reduced stimulus response (p = 0.01) and increased ataxia (p = 0.05). No horses became recumbent or displayed signs of excitement. Baseline BIS was 92 ± 4 (mean ± SD), decreased significantly after butorphanol administration (p < 0.001), and did not change significantly at any other evaluation point. Between-horse sedation scores were weakly correlated with BIS (r = −0.206; 95%CI: −0.664, 0.364; p = 0.478). Within-horse sedation scores were moderately correlated with BIS (r = −0.617; 95%CI: −0.756, −0.425; p < 0.001).ConclusionIn conclusion, the sequential addition of low-dose CRIs of butorphanol and midazolam to detomidine CRIs is associated with a stepwise increase in sedation and ataxia. Sedation score was not predicted by BIS. When sedating horses, low-dose midazolam may be added to improve sedation and reduce stimulus response, but the risk of pronounced ataxia should be considered.